Perancangan Sistem Fungsi Arsitektur Tanaman Berbasis Website Interaktif - Sanger, Philia Anastasia; Krisnandika, Anak Agung Keswari; Himawan, Cindy Kristiya; Kohdrata, Naniek (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 4 No 1 (2023): JITTER, Vol.4, No.1, April 2023, 2023)
Plants have various functions for human life which are generally used as architectural functions. Information regarding this utilization can be obtained from various sources such as encyclopedias, journals, and with the development of the times, this information can also be found through a technology called a website. Currently there is no specific website that discusses the function of plant architecture and its care, so this research was conducted to produce a website that includes this information. This study uses the research and development method with a qualitative approach which aims to create a website with information that has been filtered first through a collection of plant data and their functions originating from the major of Landscape Architecture. The results of the research are in the form of website pages that can convey information on the architectural functions of plants simultaneously along with the characteristics of the plants